The Use of Vlogging (Video Blogging) to Encounter Students' Speaking Anxiety - Fausen; Chairuddin; Maulana Yusuf Aditya (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2022)
The ability of most senior high school students in Speaking English is still average and even tends to be low.Many students anxious to speak English. They think that English is difficult. Apart of theirintelligence, the environment is also very influential in the development of students' speaking abilities. In order to overcome this problem, the utilization of vlogging could be useful to help the students to improve students’ speaking anxiety, especially in explanation text which has medium difficulty. The purpose of this study is to improve the students speakinganxiety. This study was involved 31 eleventh grade students of MA Raudlatul Ulum. This study was a classroom action research which is consisted of 1 cycles. Each cycle of this study involved of 2 meetings. During each cycle, the students have some stages to make their speaking improved. The result showed that the improvement of preliminary test to cycle test 1 was 25.9%improvement or 51,6% of total students of the students who do not already passed the criteria of success. This result proved that 1 cycle of the utilization vlogging still not yet to improve students’ anxiety in speaking explanation text.However, the next cycle cannot be done because of the corona virus